Particularly dangerous offenders in Finland – need for substance use rehabilitation?. Issue 5 (3rd September 2021) - Joelsson, Petteri; Repo, Katja; Ahlgrén-Rimpiläinen, Aulikki
ABSTRACT: In Finland, the court can refer perpetrators for a forensic mental examination to estimate whether they are considered 'particularly dangerous to life, health or freedom of another.' This impacts the punishment that perpetrators face. Examinations are conducted in psychiatric hospitals with forensic expertise. We reviewed all examinations conducted between the years 2006 and 2019 in Finland. Data concerning sex, nationality, age, psychiatric morbidity and criminal history of the subjects, conclusion of the level of dangerousness and the utilisation of structured risk assessment tools were obtained. A total of 111 examinations were conducted, 97% of which concluded that the subject was dangerous. Structured risk assessment tools were widely used. The subjects showed a high rate of comorbid substance use and personality disorders (89%). Most subjects were intoxicated during the offence and had a previous criminal history. The Finnish legal system seemingly does not segregate dangerous offenders from non-dangerous offenders. We suggest that the conclusions of the examinations should include a recommended risk prevention plan or treatment options. Based on our findings, substance-use rehabilitation and counselling could be suggested for many high-risk offenders in Finland.